2017
DOI: 10.1038/s41598-017-08896-w
|View full text |Cite
|
Sign up to set email alerts
|

Variations in biocorona formation related to defects in the structure of single walled carbon nanotubes and the hyperlipidemic disease state

Abstract: Ball-milling utilizes mechanical stress to modify properties of carbon nanotubes (CNTs) including size, capping, and functionalization. Ball-milling, however, may introduce structural defects resulting in altered CNT-biomolecule interactions. Nanomaterial-biomolecule interactions result in the formation of the biocorona (BC), which alters nanomaterial properties, function, and biological responses. The formation of the BC is governed by the nanomaterial physicochemical properties and the physiological environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…However, when CNTs interact with proteins, their effects on structural changes of proteins and associated cytotoxicity are not comprehensively understood. In this regard, the results of Ge et al,46 Ebrahim-Habibi et al,47 and Raghavendra et al48 displayed that the interaction of proteins with SWCNTs would be dictated by functional groups on nanotube surface, which will be very effective in controlling the cytotoxicity of SWCNTs. On the other hand, the results of Du et al49 demonstrated that SWCNTs caused the aggregation of lysozyme protein with a change in the protein structure.…”
Section: Discussionmentioning
confidence: 99%
“…However, when CNTs interact with proteins, their effects on structural changes of proteins and associated cytotoxicity are not comprehensively understood. In this regard, the results of Ge et al,46 Ebrahim-Habibi et al,47 and Raghavendra et al48 displayed that the interaction of proteins with SWCNTs would be dictated by functional groups on nanotube surface, which will be very effective in controlling the cytotoxicity of SWCNTs. On the other hand, the results of Du et al49 demonstrated that SWCNTs caused the aggregation of lysozyme protein with a change in the protein structure.…”
Section: Discussionmentioning
confidence: 99%
“…ENMs rarely stay put under various environmental conditions or inside cells, tissues, and organs, even for those conventionally considered to be stable (e.g., SiO 2 , MoS 2 , CdSe, graphene oxide, rare earth oxides, Ag, etc.). The first thing that happens when ENMs are introduced to the biological environments is the formation of protein/lipid corona, which will change the properties of ENMs immediately and impact the bioavailability and biodistribution as well as safety profiles, [52][53][54][55][56] and transformations (morphology, speciation, oxidation/reduction states, dissolution, recrystallization/reformation, etc.) can remarkably alter their physicochemical properties, and consequently, their fate, transport, and biological effects.…”
Section: Elucidation Of Transformation Processesmentioning
confidence: 99%
“…The majority of experimentation regarding biological responses to NPs has been performed in normal, healthy scenarios. However, clinical applications will result in the introduction of NPs into diseased environments with altered circulating biomolecules, which may influence NP–BC formation and subsequent cellular responses (Raghavendra, Fritz, Fu, Brown, & Shannahan, ; J. H. Shannahan et al, ). A study of iron‐oxide NPs compared the differential cellular effects of BCs formed within healthy or hyperlipidemic serum (J. H. Shannahan et al, ).…”
Section: Endothelial Cellsmentioning
confidence: 99%